The Relationship of Dental Malformation with Bullying and the Level of Self-Esteem among a Sample of Adolescents in Amman– Jordan : (Original Article) - Smadi, Entisar Yosef; Smadi, Rania Jamil (Dirasat: Human and Social Sciences, 2024)
Objectives: Dental deformities are associated with an unacceptable appearance and subsequent psychological effects. This is what the research found through work, and therefore they sought to identify the impact of this on the occurrence of bullying and the level of self-esteem. Methods: The study sample included108 teenagers aged between 12-20 years who suffer from dental deformities, to identify the extent of their exposure to bullying, and to study the effect of this on their level of self-esteem. The sample was taken from the orthodontic clinic affiliated with the Royal Medical Services. The study scale consisted of two parts, one to measure bullying and the other to measure self-esteem applied to a sample of patients. The descriptive correlational method was used to achieve the purposes of the study. Results: The results of the statistical analysis showed that adolescents who suffer from dental malformation are subjected to bullying, and they suffer from low self-esteem, the statistical analysis did not show statistically significant difference for the gender variable or the type of dental distortion in bullying or self-esteem. Conclusions: As a result of the study sample suffering from dental deformities and its impact on their low level of self-esteem and their exposure to bullying, they need to obtain psychological counseling services that contribute to improving their level of self-esteem and raising the efficiency of their ability to self-assertive.